Associations of Vascular Risk and Amyloid Burden with Subsequent Dementia. Issue 4 (3rd August 2022) - Gottesman, Rebecca F.; Wu, Aozhou; Coresh, Josef; Knopman, David S.; Jack, Clifford R.; Rahmim, Arman; Sharrett, A. Richey; Spira, Adam P.; Wong, Dean F.; Wagenknecht, Lynne E.; Hughes, Timothy M.; Walker, Keenan A.; et al.
Abstract : Objective: Midlife vascular risk factors (MVRFs) are associated with incident dementia, as are amyloid β (Aβ) deposition and neurodegeneration. Whether vascular and Alzheimer disease‐associated factors contribute to dementia independently or interact synergistically to reduce cognition is poorly understood. Methods: Participants in the Atherosclerosis Risk in Communities–Positron Emission Tomography study were followed from 1987–1989 (45–64 years old) through 2016–2017 (74–94 years old), with repeat cognitive assessment and dementia adjudication. In 2011–2013, dementia‐free participants underwent brain magnetic resonance imaging (with white matter hyperintensity [WMH] and brain volume measurement) and florbetapir (Aβ) positron emission tomography. The relative contributions of vascular risk and injury (MVRFs, WMH volume), elevated Aβ standardized uptake value ratio (SUVR), and neurodegeneration (smaller temporoparietal brain regions) to incident dementia were evaluated with adjusted Cox models. Results: In 298 individuals, 36 developed dementia (median follow‐up = 4.9 years). Midlife hypertension and Aβ each independently predicted dementia risk (hypertension: hazard ratio [HR] = 2.57, 95% confidence interval [CI] = 1.16–5.67; Aβ SUVR [per standard deviation (SD)]: HR = 2.57, 95% CI = 1.72–3.84), but did not interact significantly, whereas late life diabetes (HR = 2.50, 95% CI = 1.18–5.28) and Aβ independently predicted dementia risk. WMHs (per SD: HR = 1.51, 95% CI = 1.03–2.20) and Aβ SUVR (HR = 2.52, 95% CI = 1.83–3.47) independently contributed to incident dementia, but WMHs lost significance when MVRFs were included. Smaller temporoparietal brain regions were associated with incident dementia, independent of Aβ and MVRFs (HR = 2.18, 95% CI = 1.18–4.01). Interpretation: Midlife hypertension and late life Aβ are independently associated with dementia risk, without evidence for synergy on a multiplicative scale. Given the independent contributions of vascular and amyloid mechanisms, multiple pathways should be considered when evaluating interventions to reduce the burden of dementia. ANN NEUROL 2022;92:607–619